Why we must take back ownership of the EYFS. (2nd July 2019) - Allingham, Sue
Abstract : While our early years curriculum is broad and far ranging, looking at developmentally appropriate practice from birth, we are rapidly losing this in the rush to assess and level, says Dr Sue Allingham.